The Role of Classroom Teachers in the Formation of Morals in Early Childhood at State Kindergarten 1 Katilombu - Kiranti, Wa Ode Iren; Rusli, Rusli; Yahya, Safaruddin (Journal of English Language and Education, 2026)
This study sought to ascertain the ways in which early childhood moral development is influenced by class instructors at Katilombu 1 State Kindergarten.  Using procedures for documentation, interviews, and observation, a descriptive qualitative approach was adopted.  The findings show that educators have a role in guiding kids, serving as role models (models or examples), and helping kids develop high moral standards. However, there are also obstacles such as parental busyness, the environment, and the mass media. However, through a consistent approach, the formation of children's moral character is effectively instilled, positive habits are formed, social skills are developed, discipline is developed, and a sense of responsibility grows.